Carcinoma in situ and treatment options - (:unkn) unknown (Kluwer Academic Publishers, 1996)
Carcinoma in situ (CIS) is a high-grade and aggressive manifestation of transitional-cell carcinoma of the bladder that has a highly variable course. The treatment of CIS has undergone dramatic changes since this malignancy was first recognized. While cystectomy was once recommended as the initial treatment of choice, recognition of the highly variable prognosis and the uniformly high response rate to intravesical BCG has prompted a more conservative approach to management. Patients who fail BCG immunotherapy without evidence of progression may yet be candidates for intravesical chemotherapy, photodynamic therapy, or alternative immunotherapies such as alpha-2b interferon, bromopirimine, or keyhole limpet haemocyanin.